2013
DOI: 10.1002/ptr.5050
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum perforatum : Pharmacokinetic, Mechanism of Action, Tolerability, and Clinical Drug-Drug Interactions

Abstract: Hypericum perforatum (HP) belongs to the Hypericaceae family and is one of the oldest used and most extensively investigated medicinal herbs. The medicinal form comprises the leaves and flowering tops of which the primary ingredients of interest are naphthodianthrones, xanthones, flavonoids, phloroglucinols (e.g. hyperforin), and hypericin. Although several constituents elicit pharmacological effects that are consistent with HP's antidepressant activity, no single mechanism of action underlying these effects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 161 publications
1
112
0
16
Order By: Relevance
“…John's Wort (Hypericum perforatum L.) is a perennial herb belonging to the Hypericaceae family (Ruhfel et al 2013), native to Europe, Asia, and North Africa, introduced and naturalized in North America and in temperate areas of the Southern hemisphere (Carrubba and Scalenghe 2012). H. perforatum and related species have been used since ancient times as a local resource for medicinal purposes, due to their wound healing, mild sedative, antiviral, and antidepressant properties (Russo et al 2014). These properties are associated with a group of hydrosoluble metabolites, mostly accumulated in flowers: the phenolic compounds naphthodianthrones, including hypericin and pseudohypericin, and the phloroglucinol derivative hyperforin (Lazzara et al 2015).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…John's Wort (Hypericum perforatum L.) is a perennial herb belonging to the Hypericaceae family (Ruhfel et al 2013), native to Europe, Asia, and North Africa, introduced and naturalized in North America and in temperate areas of the Southern hemisphere (Carrubba and Scalenghe 2012). H. perforatum and related species have been used since ancient times as a local resource for medicinal purposes, due to their wound healing, mild sedative, antiviral, and antidepressant properties (Russo et al 2014). These properties are associated with a group of hydrosoluble metabolites, mostly accumulated in flowers: the phenolic compounds naphthodianthrones, including hypericin and pseudohypericin, and the phloroglucinol derivative hyperforin (Lazzara et al 2015).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…1A), an active ingredient of St. John's wort, which is a widely used and well investigated medicinal plant (Wolfle et al, 2014). Hyperforin is a multitarget compound that modulates various molecular functions and exerts various beneficial effects, showing antimicrobial, anti-inflammatory, anticancer, and antidepressant activity (Russo et al, 2014). It has been previously reported that hyperforin exerts antidepressant and neurotrophic effects via activation of TRPC6 in neurons (Leuner et al, 2007Griesi-Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For most high quality products, the exact quantity of Hyperforin (which is the main chemical responsible for interactions) is known. Choosing a product with negligible amounts of Hyperforin is, therefore, recommended when a patient is using pharmaceutical medications that can potentially interact 19 .…”
Section: Appling Ebm To the Clinical Practise Of Herbal Medicinementioning
confidence: 99%